A Facile and Versatile Approach to Double N‐Heterohelicenes: Tandem Oxidative CN Couplings of N‐Heteroacenes via Cruciform Dimers1. Issue 18 (13th March 2015) - Sakamaki, Daisuke; Kumano, Daisuke; Yashima, Eiji; Seki, Shu
Abstract Novel double N‐hetero[5]helicenes that are composed of two nitrogen‐substituted heteropentacenes are synthesized by tandem oxidative CN couplings via the cruciform heteropentacene dimers. The developed method is very facile and enables the synthesis of a double helicene in only two steps from commercially available naphthalene derivatives. These double N‐hetero[5]helicenes have larger torsion angles in the fjord regions than typical [5]helicenes, and optical/electrochemical measurements revealed a significant increase in the electronic communication between the two heteropentacene moieties of the double helicenes compared with their cruciform dimers. The optical resolution of one of the double helicenes was successfully carried out, and their stability towards racemization was remarkably higher than those of typical [5]helicenes. The synthetic strategy proposed in this paper should be versatile and widely applicable to the preparation of double helicenes from other N‐containing π‐conjugated planar molecules.